Areca Catechu Biochar and Nano-Biochar as Adsorbents for Congo Red: Synthesis, Characterization, and Performance Evaluation - Adawiyah, Robiatul; Yuliasari, Nova; Hanifah, Yulizah; Palapa, Neza Rahayu (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
The presence of hazardous synthetic dyes such as Congo Red in industrial wastewater poses a significant environmental threat. This study explores the potential of biochar (BC) and nano-biochar (nano-BC), derived from Areca catechu husk as sustainable adsorbents for dye removal. Nano-BC was synthesised via hydrothermal carbonisation and mechanical ball milling, leading to enhanced structural and surface properties. X-ray Diffraction (XRD) revealed that the Pinang husk is predominantly amorphous, while BC exhibits increased crystallinity with sharp peaks, and nano-BC demonstrates the highest crystallinity and nanostructural refinement. Fourier Transform Infra Red (FTIR) confirmed the transformation of aliphatic-rich raw biomass into aromatic-dominant structures in BC and nano-BC, with nano-BC showing more pronounced graphite-like features. Scanning Electron Microscope (SEM) illustrated the morphological evolution, with nano-BC exhibiting refined, uniformly porous structures. BET analysis revealed that nano-BC has a significantly higher surface area 41.38 m²/g and smaller pore size 8.4928 nm compared to BC 22.38 m²/g and 15.39 nm, enhancing adsorption capacity. Furthermore, the adsorption kinetics followed the pseudo-second-order model, and isothermal analysis confirmed monolayer adsorption with the highest maximum adsorption capacity (Qmax = 154.526 mg/g). These findings highlight the superior adsorption performance of nano-BC, emphasising its potential for environmentally friendly water treatment applications. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).